Titanium noir : [large type] a novel - Harkaway, Nick, 1972- (Random House Large Print, 2023)
"Cal Sounder is a detective working for the police on certain very sensitive cases. So when he's called in to investigate a homicide at a local apartment, he is surprised at first to see that the victim appears to be a rather typical, milquetoast techie. But on closer inspection, he finds the victim is over seven feet tall. And even though he doesn't look a day over thirty, he is actually ninety years old. Clearly, he is a Titan-one of this dystopian, near-future society's genetically-altered elites. There are only a few thousand Titans worldwide, all thanks to Stefan Tonfamecasca's discovery of the controversial T7 genetic therapy, which elevated his family to near godlike status. A dead Titan is big news . . . a murdered Titan is unimaginable. But Titans are Cal's specialty. In fact, his ex-girlfriend, Athena, is a Titan. And not just any Titan-she's Stefan's daughter, heir to the Tonfamecasca empire. As Cal digs deeper into the murder investigation, he begins to unweave the complicated threads of what should have been a straightforward case, and it soon becomes clear he's on the trail of a crime whose roots run deep into the dark heart of the world. Titanium Noir is a tightly woven, intricate tale of murder, betrayal, and vengeance"--